PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS ETNOMATEMATIKA BANJAR MATERI SEGIEMPAT DAN SEGITIGA - Norhaliza Norhaliza; Rahmatya Nurmeidina; Soraya Djamilah (Hipotenusa Journal of Research Mathematics Education (HJRME), 2022)
This research aims to explain the development process, validity, and practicality of student worksheets containing Banjar ethnomathematics on quadrilateral and triangle material. This type of research is development research, using the Plomp model, which consists of five phases: the initial investigation phase, the design phase, the realization/construction phase, the test phase, the evaluation, and the revision phase, and implementation phase. However, this development only reached the test, evaluation, and revision phases. The research instrument is a validation sheet and a practicality sheet. Three validators assessed aspects of validity 1 lecturer who is experienced in research linking culture and mathematics learning tools, 1 lecturer in geometry courses, and 1 mathematics teacher. The practical element was evaluated by 26 students and one teacher studying this material. The validation results from the validator obtained an index value of 0.77, which is included in the "medium validity" criteria. The results of the practicality test by teachers and students obtained an achievement rate of 92% and were included in the "efficient" measures. Thus, a learning tool is produced as student worksheets containing Banjar culture on quadrilateral and triangle material with proper and practical steps.